Surgery for Locked Cervical Facets: A Technical Note - Sumit Sinha; Shashank S. Kale (Indian Journal of Neurosurgery)
Abstract Cervical facet dislocations represent a severe form of cervical spine injury and can be present unilaterally or bilaterally. They are invariably associated with neurological compromise, with complete spinal cord injury seen in 65 to 87% and the incomplete injury seen in 13 to 25% of the cases. The facet dislocations represent hyperflexion–distraction injuries and are classified as type B in the AO classification system. These are unstable injuries and necessitate some form of surgical stabilization. A variety of surgical procedures can be performed to effect the reduction of the locked facets which can be performed anteriorly, posteriorly, and by combined approaches. The article focuses on the indications, contraindications, and on the surgical management and the techniques used in the reduction of unilateral or bilateral locked facets.